Arid zone of India and Pakistan: A study in its water balance and delimitation - BHATIA, SHYAM SUNDER (MAUSAM, 1957)
In this paper, a study of the water balance of the arid zone of India and Pakistan has been made that basis the arid zone itself has been delimited. The limits obtained have been compared with the limits suggested by different authors.